Small Localities at the Outskirts of Europe: Transnational Mobilities, Diversification and Multi-Scalar Place-Making - (:unkn) unknown (My University, 2025)
Research on the Migration-Mobility Nexus has mainly focused on global cities embedded in globalized neoliberal economies and transnational spaces. These studies have two limitations. First, they ignore the transformation engaged outside urban centers. Second, the size and complexity of large urban cities obscure the dynamics by which diverse forms of mobility generate social diversity, and how, in turn, these participate to social transformation. Consequently, we propose to study these questions at the scale of small localities – villages, conglomerations of villages, or valleys – at the outskirts of Europe, including their entire population (migrants and non-migrants, mobile as well as non-mobile people). We investigate all forms of mobilities coexisting in one small locality (internal out- and immigration, tourism, old-age-retired expats, sedentary and commuters, international migrants, mobile business people, refugees, etc.). As a whole, we aim to understand how these types of dynamics – transnational, in terms of boundary work, and in terms of individual live trajectories – enable, constrain, guide, or open new possibilities for each other. Our overall objective is to develop an integrative theoretical model to understand new facets of the Migration-Mobility Nexus and current globalizing forces. In order to develop a comparative analysis, we plan to conduct four case studies in Switzerland, in Greece, in the Czech Republic and in Denmark.
Keywords: Mobility; case studies; transnationalism; boundary work; lifecourse